Sociodemographic disparities in the establishment of health records among 0.5 million migrants from 2014 to 2017 in China: a nationwide cross-sectional study - Jun Wang; Jingmin Zhu; Xueyao Wang; Yue Che; Yang Bai; Jue Liu (BMC, 2021)
Abstract Background Migrants account for a large part of China's population. Many policies and inventions have been taken to improve access to public health services and the health of migrants. China's Basic Public Health Services(BPHS) are a series of public health services in this policy domain, which aims at promoting the access of public health sevices and improve health equity of residents. The establishment of health records is the fundamental service of BPHS. However, there is little known about the establishment of health records among migrants in China, which hinders the more efficient provision of health services for migrants, and health equity is difficult to achieve. Based on the research gap, this study aims at showing the sociodemographic disparities in the establishment rate of health records, and identifying priorities and recommendations for promoting health equity of migrants in China. Methods This study used national data from China Migrants Dynamic Survey (CMDS) from 2014 to 2017 to evaluate the sociodemographic disparities in the establishment rate of health records and utilization of relevant public health services. The study included 539,926 respondents. Following the descriptive statistics of migrants, we showed the establishment rate of health records by sociodemographic characteristics and migrating related characteristics. Multivariate analysis was conducted to explore the associations between sociodemographic charicteristics, migrating related charicteristics and the establishment of health records. Results The establishment rate of health records among migrants in the sampled years were 22.99, 38.44, 27.29% respectively, and 29.18% in general, and there existed heterogeneity in the establishment rate of health records by sociodemographic charicteristics and migrating related charicteristics. Female migrants who were older, from middle age, married or living with partner, with higher educational attainment, with urban household registration, migrated for longer time, migrated for the reason of studying or family issues, migrated in province were more likely to establish health records. Conclusion There existed sociodemographic disparities in the establishment rate of health records and inequalities in the utilization of health records services among migrants in China. Migrating related characteristics also had impact on the establishment status. Policies should take both supply side and demand side of health services to improve the health equity of migrants, which means that relative departments should continue to invest in primary healthcare centers to improve their ability to provide services as well as migrants' health literacy.